General Confiscation Versus Criminal Confiscation in Regard to Curators’ Authority and Responsibility in Bankruptcy Settlement Process - Elli Ruslina; Siti Rodiah; Benny Wulur (Fakultas Hukum, Universitas Warmadewa, 2020)
The process of bankruptcy general confiscation sometimes clashes with criminal confiscation process. The present study aims to look at curators’ authority and responsibility to sell bankrupt properties, which have been confiscated by investigating officers in a case of criminal confiscation. It also delves into the legal ramifications that may occur and into the concepts of bankruptcy settlement. This study employs a juridical normative method and the necessary legal material are collected through literature study. The legal material are analyzed in juridical qualitative approach, using a comparison between bankruptcy laws in several countries. Based on the result of this study, it is concluded that curators’ authority and responsibility are still applicable even though they are subject to appeal. The legal consequences in the case that bankrupt estate is being confiscated by investigating officers due to the conflict between criminal confiscation and general confiscation require the court to prioritize the criminal confiscation. Once it is resolved, bankruptcy assets/estate are returned to the curator. This study recommends that there should be an effort to legally synchronize and harmonize Article 39 Point (2) of KUHAP (Indonesian Law of Criminal Procedure) with Article 31 Point (2) of Law No. 37 Year 2004 Concerning Bankruptcy and PKPU (Suspension of Payment/Debt Moratorium). One of the solutions offered in this study is by implementing E-Court, as is the case in Indonesia’s Constitutional Court, especially in Commercial Court whose habitat is digital and that handles legal problems pertaining to creative economy.